View of town with men in the foreground working with machinery - De Santis, Giuseppe, 1917-1997 (Z. Smith Reynolds Library, Wake Forest University, 1958)
This film was never made because of funding difficulties. A 15 minute screen test with Claudia Cardinale was made.
Keywords: Motion pictures -- Italy -- History -- Sources; Motion picture producers and directors -- Italy; Stills (motion pictures); Motion picture actors and actresses -- Italy